Trabecular bone score, bone mineral density and fracture risk in women with rheumatoid arthritis (pilot study) - M. V. Kozyreva; O. V. Dobrovolskaya; N. V. Demin; O. A. Nikitinskaya; N. V. Toroptsova (Научно-практическая ревматология)
The aim – to assess bone mineral density (BMD) and microarchitecture, as well as the risk of fractures in postmenopausal women with rheumatoid arthritis (RA). Materials and methods: 95 postmenopausal women (mean age 62.3±8.1 years) with a confirmed RA were included. All patients underwent a questionnaire, clinical and laboratory examination, dual-energy X-ray absorptiometry (DXA) of the lumbar spine (L1–L4), proximal femur, and trabecular bone score (TBS) assessment. The 10-year probability of osteoporotic fracture was calculated using the FRAX tool without including femoral neck (FN) BMD (BMD–), with FN BMD (BMD +) and additionally adjustment for TBS (BMD + TBS). Results. Osteoporosis (OP) was found in 41 (43.2%) patients: in L1–L4 – in 26,3%, in FN – in 22.1%, and in the total hip (TH) – in 11.6% persons. Degraded microarchitecture according to TBS was found in 38.9% of patients, partially degraded – in 25.3%, and normal – in 35.8% of women with RA. A high risk of fracture according to FRAX BMD– was detected in 49.5% of patients. TBS correlated with age (r=–0.30; p=0.003), duration of postmenopausal period (r=–0.26; p=0.014), cumulative dose of glucocorticoids (GCs) (r=–0.34; p=0.045), FRAX BMD– (r=–0.24; p<0.05) and FRAX BMD+ (r=–0.21; p<0.05); L1–L4 BMD (r=0.43; p<0.001), FN BMD (r=0.21; p=0.038), TH BMD (r=0.23; p=0.02). Low TBS was significantly more often detected in people with a history of fractures compared to people without them (p<0.05). Among RA patients with normal L1–L4 BMD 9.5% of persons had degraded microarchitecture of bone tissue according to TBS. The inclusion of TBS in FRAX increased the risk of fractures to high in 9.5% of patients and reduced it to low in 7.4% of women, due to which the total number of people with RA who had a high risk of fractures became 54.7%. Conclusion. OP was diagnosed in 43.2%, and degraded microarchitecture of bone tissue according to TBS – in 38.9% of postmenopausal women with RA. A high risk of fractures according to FRAX was found in 49.5%. TBS negatively correlated with age, duration of postmenopause, cumulative GCs dose, FRAX fracture risk, and positively correlated with BMD in all measurement sites. The FRAX adjustment by TBS redistributed patients in risk groups, as a result of which 54.7% of RA patients needed anti-osteoporotic treatment.